The Current and Future Potential of Transcranial Magnetic Stimulation With Electroencephalography in Psychiatry. Issue 4 (30th August 2019) - Hui, Jeanette; Tremblay, Sara; Daskalakis, Zafiris J.
Abstract : The search for biological targets in psychiatric disorders is essential to better understand illness mechanisms and also to monitor and predict response to currently available therapeutic interventions. To this end, the combination of transcranial magnetic stimulation with electroencephalography (TMS‐EEG) has emerged as a powerful clinical research tool. TMS‐EEG allows cortical properties, such as excitability, inhibition, oscillatory activity, and connectivity, to be directly probed within a specific region of the cortex. This review will summarize the state of the current literature on TMS‐EEG and its potential to uncover biological targets in psychiatric illnesses, with a focus on major depressive disorder, bipolar disorder, and schizophrenia. Collectively, the reviewed studies suggest that alterations in gamma‐aminobutyric acid‐mediated inhibition and gamma oscillations in the dorsolateral prefrontal cortex and neighboring frontal regions are potential shared biomarkers in psychiatry, highlighting the potential of TMS‐EEG to help identify translational biomarkers.